1990
DOI: 10.3758/bf03197102
|View full text |Cite
|
Sign up to set email alerts
|

Learning subgoals and methods for solving probability problems

Abstract: We hypothesize that typical example problems used in quantitative domains such as algebra and probability can be represented in terms of subgoals and methods that these problems teach learners. The "quality" ofthese subgoals and methods can vary, depending on the features ofthe examples. In addition, the likelihood of these subgoals' being recognized in novel problems and the likelihood of learners' being able to modify an old method for a new problem may be functions of the training examples learners study. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
0
1

Year Published

1994
1994
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(64 citation statements)
references
References 32 publications
3
60
0
1
Order By: Relevance
“…The second possible explanation is that the modified final goal furnishes an implicit cue for constructing the subgoal. In other words, the fact that the rectangles appear together in the final goal cues moving them together to form the subgoal without any explicit thought on the matter necessarily taking place (Catrambone, 1994(Catrambone, , 1995Catrambone & Holyoak, 1990). Our results support either one of these interpretations.…”
Section: Resultssupporting
confidence: 81%
See 1 more Smart Citation
“…The second possible explanation is that the modified final goal furnishes an implicit cue for constructing the subgoal. In other words, the fact that the rectangles appear together in the final goal cues moving them together to form the subgoal without any explicit thought on the matter necessarily taking place (Catrambone, 1994(Catrambone, , 1995Catrambone & Holyoak, 1990). Our results support either one of these interpretations.…”
Section: Resultssupporting
confidence: 81%
“…What we would like to underline is that what was studied in this research was more the means (goal structure) or procedure that allowed the goal to be reached than the goal state itself. The same is true for the studies of Catrambone (1994Catrambone ( , 1995, Catrambone and Holyoak (1990), and Ross (1987Ross ( , 1989, which focused more on procedure than on the final goal. In these studies, the negative role ofgoal dissimilarity was studied through a dissimilarity of procedures.…”
mentioning
confidence: 81%
“…A number of studies have shown that manipulations of examples have a powerful and systematic effect on performance on novel problems (e.g., Catrambone & Holyoak, 1990;LeFevre & Dixon, 1986;Pirolli & Anderson, 1985;Reder, Charney, & Morgan, 1986;Ross, 1984). Given the central role that examples play in prob-IMPROVING EXAMPLES 607 lem solving, and given the assumption that people learn subgoals from the examples, it is important to investigate the conditions that influence subgoallearning.…”
Section: Learning From Examplesmentioning
confidence: 99%
“…The term subgoal is used here to represent the task structure to be learned for solving problems in a particular domain (e.g., Catrambone & Holyoak, 1990;Dixon, 1987;Eylon & Reif, 1984). A subgoal groups a set of steps under a meaningful task or purpose (e.g., Anzai & Simon, 1979;Chi & VanLehn, 1991).…”
Section: Georgia Institute Of Technology Atlanta Georgiamentioning
confidence: 99%
“…When people solve complex problems, it is common to generate sub goals for achieving major aspects ofthe task and to attempt to solve each of the subgoals as separate problems (see, e.g., Newell & Simon, 1972). For example, when attempting to calculate the probability of an event in a probability problem, subjects may generate the subgoal offirst finding the overall frequency of the event and then after that subgoal has been achieved, divide by the total number of trials to solve the original problem (Catrambone & Holyoak, 1990). Catrambone (1994Catrambone ( , 1995 has argued that the appropriate use of subgoals in problems like this promotes transfer: Learners are able to generalize to novel tasks more readily because they can find new solution methods to achieve the same sequence of subgoals.…”
Section: Discussionmentioning
confidence: 99%